ANALISIS KAPASITAS RUANG PARKIR OFF STREET DI PLAZA ASIA KOTA TASIKMALAYA - heryana, refalia; sumarno, wahyu; saepudin, uu (Jurnal Ilmiah Teknik Sipil, 2024)
Plaza Asia is located on Jalan HZ Mustofa No. 326 Tugujaya, Cihideung District, Tasikmalaya City is a shopping center that offers a variety of shops and outlets. Plaza Asia Kota Tasikmalaya has several off street parking lots, including the main parking lot for motorcycles and the building’s main parking lot for cars. During peak hours, it is seen that the main parking lot for motorcycles and building parking lots often exceed the capacity they should, so it is necessary to analyze the availability of the main parking lot for motorcycles and the main parking lot for cars in Plaza Asia Kota Tasikmalaya. The method used in this study is the observation method. The observation method is carried out by means of direct surveys in the field. Primary data Primary data is data obtained from the results of field surveys, including parking accumulation, parking volume, and parking duration. The secondary data is the Plaza Asia Plan of Tasikmalaya City. Based on data analysis and discussions that have been carried out, it can be concluded that the capacity of Plaza Asia Tasikmalaya off-street parking spaces has a land area of 1,441,125 for motorcycles and 3,016.45 for cars. The volume of motorcycle parking is 2482 vehicles and cars are 1294 vehicles. The accumulated parking lot of motorcycles was 1,073 vehicles and cars were 306 vehicles. The duration of parking motorbikes is 552 minutes and cars are 484 minutes. The largest parking index for motorcycles was 182.48% and cars was 100.33%. The static capacity of off street parking spaces in Plaza Asia Kota Tasikmalaya resulted in the number of motorbike parking of 588 SRP and cars of 305 SRP. And for dynamic capacity obtained by direct survey to the field, the largest dynamic capacity of motorcycles occurred on Tuesday at 3918.54 and the smallest on Saturday at 2991.81. The largest dynamic capacity of the car occurred on Tuesday at 2488.17 and the smallest occurred on Sunday at 1631.87. Based on the conclusions obtained from the analysis above, it is necessary to optimize parking spaces on weekdays and weekends. And installed traffic signs are prohibited from parking on the road body along the Plaza Asia area of Tasikmalaya City.